Hemorrhoidal Disease - The Role of Dietary, Behavioral and Lifestyle Factors in Prevention and Conservative Management - Włodarczyk, Michał (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Hemorrhoidal disease is a common anorectal condition affecting quality of life and frequently leading to medical consultation. Its pathogenesis is multifactorial, involving vascular, connective tissue and neuromuscular alterations, as well as modifiable lifestyle factors. This review aims to summarize current evidence on dietary, behavioral and lifestyle factors in the prevention and conservative management of hemorrhoidal disease. Materials and methods: A literature review was conducted using PubMed and Google Scholar, focusing primarily on studies published in English and prioritizing systematic reviews, meta-analyses, randomized controlled trials and observational studies. State of knowledge: Chronic constipation, straining, prolonged toilet sitting, low fiber intake, inadequate hydration, obesity, smoking and certain dietary patterns contribute to hemorrhoidal disease. Fiber-rich diets, adequate fluids and moderate physical activity improve bowel function and reduce mechanical stress. Behavioral factors, including toilet posture and avoidance of prolonged sitting, also play a role. Emerging evidence suggests gut microbiota may influence disease development. Conclusions: Conservative management should focus on lifestyle and behavioral modifications. Adequate hydration, fiber intake, weight management, smoking cessation, physical activity and proper bowel habits form the basis of non-invasive management. A holistic, patient-centered approach may reduce symptom severity, prevent progression and limit the need for surgical interventions.